Biomechanical Comparison of Spacer Pin Fixation to Two Established Methods of Tibial Tuberosity Transposition Stabilization in Dogs - Sullivan, Anna Lia; Ordway, Nathaniel R.; Park, Brian H.; Natsios, Pavlos; Petazzoni, Massimo; Tinga, Selena (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objective The aim of this cadaveric study was to compare the biomechanical outcomes of three methods of stabilization for tibial tuberosity transposition to treat medial patellar luxation: a complete osteotomy with a two-pin and tension band wire (TBW) fixation (TBW group), a partial osteotomy with a two-pin fixation (2 Pin group), and a partial osteotomy with a spacer pin fixation (Spacer Pin group).Study Design Thirty medium to large-sized canine cadaveric tibiae were dissected and randomly assigned to one of three groups: TBW, 2 Pin, and Spacer Pin groups. The patellar ligaments were loaded in tension until ultimate failure. Ultimate failure force and mode of failure were documented, stiffness was calculated, and the results were compared statistically between the three treatment groups.Results There were not any significant differences in ultimate failure force or stiffness between groups. All groups predominantly failed by patellar ligament failure, with distal tibial crest fracture/displacement being the second-most common mode in the 2 Pin and Spacer Pin groups.Conclusion The mechanical properties of the spacer pin stabilization were not different from the TBW and 2 Pin groups. The spacer pin technique could be an alternative way to stabilize tibial tuberosity following tibial tuberosity transposition with a partial osteotomy based on this cadaveric load-to-failure model.
Keywords: biomechanics; orthopaedic surgery; patellar luxation; tibial tuberosity transposition; spacer pin technique